Discovering the Holy Spirit in the New Testament - Warrington, Keith (Peabody, Mass. : Hendrickson Publishers, 2005)
"In this survey, Keith Warrington delves into New Testament passages about the third person of the Trinity. When asking the question "What does this text say about the Spirit?" Warrington first exposits the text and then explores the significance of that text for the original readers. Finally, Warrington concludes each chapter with questions that reflect on the significance of these passages for today's readers. This insightful study will enable readers to articulate for themselves the vital role played by the Holy Spirit in the lives of all believers."--Book Jacket
Includes bibliographical references and indexes
Keywords: Bible. -- Theology; Holy Spirit -- Biblical teaching